2007
DOI: 10.1521/pedi.2007.21.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Coercive and Precocious Sexuality as a Fundamental Aspect of Psychopathy

Abstract: Sexual behavior is closely associated with delinquency and crime. Although psychopaths, by definition, have many short-term sexual relationships, it has not been shown that sexuality is a core aspect of psychopathy. A Darwinian view of psychopathy led to the hypothesis that psychopaths have a unique sexuality involving early, frequent, and coercive sex. Our subjects were 512 sex offenders assessed on the Hare Psychopathy Checklist (PCL-R). Five variables reflecting early, frequent, and coercive sex loaded on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 26 publications
8
114
3
2
Order By: Relevance
“…The theory is complex, but its components are testable. Moreover, the proposal of anomalous early hemispheric specialization fits not only with reported structural asymmetries but also with the left hemisphere activation deficits observed in adult psychopathic offenders 39,40 and documented language-attentionperception asymmetries. 41,42 Dr Gao and colleagues 27 also underscore the need for more physiological research on youth with psychopathic traits.…”
supporting
confidence: 78%
“…The theory is complex, but its components are testable. Moreover, the proposal of anomalous early hemispheric specialization fits not only with reported structural asymmetries but also with the left hemisphere activation deficits observed in adult psychopathic offenders 39,40 and documented language-attentionperception asymmetries. 41,42 Dr Gao and colleagues 27 also underscore the need for more physiological research on youth with psychopathic traits.…”
supporting
confidence: 78%
“…This involves sexual promiscuity and impulsive, thrill-seeking behavior to have many sexual encounters. Psychopaths invest only minimally in their partners; they also engage in sexual behavior, including sexual coercion, at early ages (Harris et al, 2007).…”
Section: Sexual Homicide and General Antisocialitymentioning
confidence: 99%
“…In a study with undergraduate students (Kosson, Kelly, & White, 1997), the items of factor 1 related to the use of physical force in sexual aggression, while those of factor 2 related to the use of talking or persuasion in order to engage in sexual activities. In another study, higher scores in sexual aggressors correlated positively with the rape of fertile aged women and negatively with pedophiles and child abusers (Harris, Rice, Hilton, Lalumiére, & Quinsey, 2007). The same study suggested a Darwinian view associating psychopathic conduct with early, coercive and frequent sex, intending reproduction.…”
Section: Resultsmentioning
confidence: 83%